Minimally invasive surgery for Achilles tendon pathologies - Nicola Maffulli; Umile Giuseppe Longo; Filippo Spiezia; et al (Dove Medical Press, 2010)
Nicola Maffulli1, Umile Giuseppe Longo2, Filippo Spiezia2, Vincenzo Denaro21Centre for Sports and Exercise Medicine, Barts and The London School of Medicine and Dentistry, London, England; 2Department of Orthopedic and Trauma Surgery, Campus Bio-Medico University, Rome, ItalyAbstract: Minimally invasive trauma and orthopedic surgery is increasingly common, though technically demanding. Its use for pathologies of the Achilles tendon (AT) hold the promise to allow faster recovery times, shorter hospital stays, and improved functional outcomes when compared to traditional open procedures, which can lead to difficulty with wound healing because of the tenuous blood supply and increased chance of wound breakdown and infection. We present the recent advances in the field of minimally invasive AT surgery for tendinopathy, acute ruptures, chronic tears, and chronic avulsions of the AT. In our hands, minimally invasive surgery has provided similar results to those obtained with open surgery, with decreased perioperative morbidity, decreased duration of hospital stay, and reduced costs. So far, the studies on minimally invasive orthopedic techniques are of moderate scientific quality with short follow-up periods. Multicenter studies with longer follow-up are needed to justify the long-term advantages of these techniques over traditional ones.Keywords: tendinopathy, rupture, percutanous repair, less invasive